The effect of actinomycin D on the megakaryocytic line in rat - Janoutová, J; Likovský, Z (Functional and developmental morphology, 1994)
Four-day administration of actinomycin D to the albino rat in daily doses of 25 micrograms/kg decreased--in relation to all blood cells of the bone marrow--the values of the more mature stages of the megakaryocytic line, i.e. megakaryocytes and naked megakaryocyte nuclei. The number of megakaryoblasts was not influenced.
Keywords: Dactinomycin; Animals; daktinomycin; počet buněk; Cell Count; Rats; Megakaryocytes; Rats, Wistar; megakaryocyty; Male; mužské pohlaví; krysa rodu Rattus; zvířata; potkani Wistar